Constraining attenuation uncertainty in common midpoint radar surveys of ice sheets. Issue 10 (22nd October 2016) - Holschuh, Nicholas; Christianson, Knut; Anandakrishnan, Sridhar; Alley, Richard B.; Jacobel, Robert W.
Abstract: For common offset radar data, there is no clear way to disentangle path effects from reflector characteristics, so efforts to determine the physical properties at the bed using reflection amplitude are inherently limited by the constraints on englacial attenuation. In this study, we identify the theoretical considerations required for interpreting bistatic radar surveys and use data collected on the Northeast Greenland Ice Stream and Kamb Ice Stream to compute local attenuation profiles. We found that failing to correct for angle‐dependent controls on return power (including antenna directivity, the reflection coefficient, and refractive focusing) can bias the computed attenuation rates as much as 30 dB/km for reflectors at 1 km depth. Because the radiation characteristics are the dominant source of uncertainty in our data, we recommend either a simplified survey design for the future (where the antennae are decoupled from the ice surface) or additional data collection to constrain the near‐field permittivity and its effect on the radiation pattern. Depth‐averaged attenuation rates computed using common midpoint methods for deep reflectors yield values >10 dB/km higher than attenuation rates computed using common offset techniques with the same data. We attribute these anomalously high attenuation rates to additional wavenumber‐dependent (and therefore, angle‐dependent) interferences between subwavelength reflectors. Key Points: Common midpoint (CMP) radar surveys can be used to constrain englacial attenuation The source and survey configurations introduce significant uncertainties in attenuation rates, especially at wide‐angles in shallow ice Radar CMP surveys tend to overestimate electromagnetic attenuation in glaciers, due to subwavelength reflector interferences and roughness